Factors Involved in Avoidance of Contraceptives - Khozama Khan, Tanzila Rafiq, Madiha Gillani, Piya Muhammad Musammat Rafi, Sidra Altaf, Faisal Mubeen, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To determine the frequency of factors involved in avoidance of contraceptive methods in multigravida female. Study Design: Cross sectional survey Place and Duration of Study: This study was conducted at the obstetrics and Gynaecology unit in Bahawal Victoria Hospital Bahawalpur from 16-08-2018 to 10-09-2019. Materials and Methods: 250 Multigravida women not practicing contraception, of Reproductive age, Para 2 or more were included in the study. All those women fulfilling the inclusion/exclusion criteria were included in the study. Software SPSS was used and Chi-Square test was applied. Frequency and percentages were calculated for factors involved in avoidance of contraceptive methods. Results: Factors involved in avoidance of contraceptive methods was recorded which shows that 6.8%(n=17) had age <18 years, 55.6%(n=139) had will of sons and 37.6%(n=94) had religious reasons. Stratification for factors involved in avoidance of contraceptive methods with regards to parity was done, 100% were between 2-5 para, Out of 139 cases having will of sons, 71.94% were between 3-5 gravidas and 28.06% had >5 gravidas and 94 cases for religious reason, 53.19% were between 3-5 gravidas and 46.81% had >5 gravidas. Conclusion: We concluded that age <18 years, will of sons and religious affiliation are the leading factors involved in avoidance of contraceptive methods in multigravida female Keywords: Avoidance of contraception, multigravida females, multiparity factors, Reproductive age <18 years, will of sons, religious reasons in multiparity.